Sports Performance and Health - Supej, Matej; Spörri, Jörg (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Sports performance is primarily associated with elite sport, however, recreational athletes are increasingly attempting to emulate elite athletes. Performance optimization is distinctly multidisciplinary. Optimized training concepts and the use of state-of-the-art technologies are crucial for improving performance. However, sports performance enhancement is in constant conflict with the protection of athletes' health. Notwithstanding the known positive effects of physical activity on health, the prevention and management of sports injuries remain major challenges to be addressed. Accordingly, this Special Issue on "Sports Performance and Health" consists of 17 original research papers, one review paper, and one commentary, and covers a wide range of topics related to fatigue, movement asymmetries, optimization of sports performance by training, technique, and/or tactics enhancements, prevention and management of sports injuries, optimization of sports equipment to increase performance and/or decrease the risk of injury, and innovations for sports performance, health, and load monitoring. As this Special Issue offers several new insights and multidisciplinary perspectives on sports performance and health, readers from around the world who work in these areas are expected to benefit from this Special Issue collection.